'Nudging' registration as an organ donor: Implications of changes in choice contexts for socio-cultural groups. (September 2015) - Morgan, Myfanwy; Deedat, Sarah; Kenten, Charlotte
Thaler and Sunstein's behavioural-economics theory of 'Nudge' aims to achieve beneficial outcomes for individuals and the society through designing the contexts in which choices are made rather than relying on traditional policy levers of restrictions, penalties and education. This article examines Nudge strategies to increase registration as a deceased organ donor among minority ethnic groups based on 22 focus groups that were held with Black and South Asian minority ethnic groups in London, UK. The article identifies ways in which minority ethnic groups' habitus appears to limit awareness and knowledge of the system of organ donation and shapes attitudes to registration, with the varying influence of faith/culture and trust in the system reflecting differences in prior contexts and experience. This questions a key requirement of Nudge in terms of its libertarian dimension and suggests that focusing on the immediate choice context and neglecting individuals' prior dispositions may not achieve desired outcomes for socially heterogeneous populations.